Wannier-Koopmans method calculations of organic molecule crystal band gaps. (4th September 2018) - Li, Shucheng; Weng, Mouyi; Jie, Jianshu; Zheng, Jiaxin; Pan, Feng; Wang, Lin-Wang
Abstract: It is important to accurately predict the band gaps of crystals, including organic crystals, with low computational cost. Despite the significant underestimation of the crystal band gap by the density functional theory (DFT), a recently proposed Wannier-Koopmans method (WKM) based on DFT calculations seems to yield accurate band gaps for a wide class of materials including common semiconductors, alkali halides and 2D materials. It is nevertheless important to test the limit of WKM, in particular in systems with unique characteristics. In this work, we apply the WKM to 10 organic small molecule crystals and find that the WKM calculated band gaps agree well with GW results. We also introduce a new way to calculate the Wannier functions in the WKM calculations.